1991
DOI: 10.1128/jb.173.19.6009-6017.1991
|View full text |Cite
|
Sign up to set email alerts
|

Physiological studies of tryptophan transport and tryptophanase operon induction in Escherichia coli

Abstract: Escherichia coli forms three permeases that can transport the amino acid tryptophan: Mtr, AroP, and TnaB. The structural genes for these permeases reside in separate operons that are subject to different mechanisms of regulation. We have exploited the fact that the tryptophanase (tna) operon is induced by tryptophan to infer how tryptophan transport is influenced by the growth medium and by mutations that inactivate each of the permease proteins. In an acid-hydrolyzed casein medium, high levels of tryptophan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
155
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(160 citation statements)
references
References 27 publications
4
155
0
1
Order By: Relevance
“…Expression of tyt1 from the inducible T5 promoter in a pQE60 derivative revealed only marginal tyrosine accumulation above background (data not shown). To generate a suitable host strain for detailed kinetic and biochemical studies, we used E. coli CY15212, a strain already deficient in the three aromatic amino acid uptake systems, Mtr, AroP, and TnaB (25), as the parental strain for the subsequent disruption of the tyrP and pheP genes. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of tyt1 from the inducible T5 promoter in a pQE60 derivative revealed only marginal tyrosine accumulation above background (data not shown). To generate a suitable host strain for detailed kinetic and biochemical studies, we used E. coli CY15212, a strain already deficient in the three aromatic amino acid uptake systems, Mtr, AroP, and TnaB (25), as the parental strain for the subsequent disruption of the tyrP and pheP genes. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is hypothesized that indole binds to the C-terminal domain of RamR and derepresses the transcriptional activity of ramA by causing detachment from the binding site of RamR. In E. coli, indole is produced from tryptophan by tryptophanase and is excreted from the cell (Yanofsky et al, 1991). Salmonella does not produce indole because it lacks the tnaA gene that encodes tryptophanase (McClelland et al, 2001); however, indole is found in various internal human environments, especially in the intestine (Sonnenwirth, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Indole, a bacterial metabolite (Yanofsky et al, 1991), is produced from tryptophan by tryptophanase (TnaA) and excreted outside the cell. Indole is a biological oxidant for bacteria, and it induces antioxidant proteins in E. coli and Brevibacterium flavum (Garbe et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Indole is produced from tryptophan by tryptophanase (encoded by tnaA) and its production is regulated by the tryptophan (trpABCDE) and tna operons (tnaCAB) [6][7][8]. The level of tryptophan controls transcription-terminating factor (Rho) that affects tna operon and indole production [6,8]. In the low tryptophan level, trp operon is elevated and tna operon is repressed, as Rho occurs in this operon resulting in low indole production.…”
Section: Introductionmentioning
confidence: 99%
“…Although indole has been reported in both Gram-negative and Gram-positive bacteria, biosynthesis of indole has been studied mostly in Escherichia coli. Indole is produced from tryptophan by tryptophanase (encoded by tnaA) and its production is regulated by the tryptophan (trpABCDE) and tna operons (tnaCAB) [6][7][8]. The level of tryptophan controls transcription-terminating factor (Rho) that affects tna operon and indole production [6,8].…”
Section: Introductionmentioning
confidence: 99%